A polyvalent mediterranean, or the trope of nomadism in the literary oeuvre of Igiaba Scego and Abdourahman A. Waberi - Benedicty-Kokken, Alessandra (RELIEF - REVUE ÉLECTRONIQUE DE LITTÉRATURE FRANÇAISE, 2017)
I argue that novelists Igiaba Scego and Abdourahman A. Waberi, building on the work among others of Nuruddin Farah, engage the trope of nomadism so as to propose a pre-colonial imaginary of a Somali polyvalent cosmopolitanism as a possible tool for thinking through our contemporary geographies of Africa, Europe, and the Middle East. Cet article propose que les romanciers Igiaba Scego et Abdourahman A. Waberi re-travaillent la thématique du nomadisme afin de créer un imaginaire somalien pré-colonial à la fois cosmopolite et polyvalent dans son cosmopolitisme. En dialogue notamment avec le romancier Nuruddin Farah, Scego et Waberi nous offrent ainsi des outils pour penser une géographie plus fluide entre l’Afrique, l’Europe et le Moyen-Orient.